Social Development, the promotion of Well-Being, and the Perceived Role of Social Work in Peru - Miriam Gerlach (Social Work & Society, 2019)
Social development can benefit from a more realistic assessment of what has, what can and what should be accomplished. This research aims at describing social development interventions and identifying the perceived role of social work in the promotion of well-being within social development interventions in Peru. To achieve this, the research method concentrated on collecting data through a desk review and a survey. The purposive sample was composed of 30 professionals working on the promotion of well-being, in public institutions, NGOs, social entrepreneurships, universities, international and national agencies and community-based organizations in Lima, the Andean and rain forest region. The results revealed that most of the organizations pursue the main goal of integral development preventing multidimensional problems, mainly through educational strategies (developing human and social capital), as well as implementing social planning and creating employment; usually with families and women. Social workers are fairly represented in the field, however perceived positively, as promoters of well-being and more equal societies. Demanding challenges lie ahead of Peruvian social development, though the results underlined valuable structural and subjective resources to overcome these.